Clinical Utility of Radiologic Disease Reassessment in the Management of Pediatric B-Cell Non-Hodgkin Lymphoma. Issue 3 (April 2021) - Green, Katherine; Pavasovic, Vesna; Ghorashian, Sara; Ancliff, Philip; Bartram, Jack; Rao, Anupama; Samarasinghe, Sujith; Vora, Ajay; Cheng, Danny; O'Connor, David
Abstract : Although outcomes for children with B-cell non-Hodgkin lymphoma are excellent, between 20% and 40% demonstrate residual radiologic abnormalities at disease assessment during consolidation therapy, the significance of which remains uncertain. The authors report the outcomes for all children treated for B-cell non-Hodgkin lymphoma at our center over an 11-year period. Twenty-four of 64 (38%) children had residual radiologic abnormalities at disease remission assessment. Seven (29%) underwent histologic biopsies that were normal. No children with residual radiologic abnormalities experienced disease relapse or death, suggesting that imaging at this time point creates clinical uncertainty without indicating residual disease or predicting relapse.